BRIDGING THE GAP ENHANCING RESEARCH-TO- COMMUNITY EXTENSION APPROACH - Elnie D. Calunsag (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
To construct a multidisciplinary framework for global education, integrating cultural understanding, psychological insights and literacy skills, a research-to- community extension approach was used as a systematic methodology to transfer research findings into practical applications. This response aims to investigate the varied nature of the research-to-community extension by examining its strengths, weaknesses, and potential improvement as Cotabato State University, a new university, intensifies its threefold functions: instruction, research, and extension. To improve the effectiveness of research -to- community extension, the researcher/project leader delves into the crucial role of community engagement in research, investing in capacity building among recipients and translating research findings into a actionable solutions for communities. Community members received a two-day training to improve their knowledge and capacity to engage in extension activities for long-term sustainability, particularly with regard to managing their children's sexual development.